Persaudaraan Sesama Muslim - Maryana Sepiana; Uss Husni Hoer; Syifa Alawiyah; Muhammad Gani Mulya Perdana (Penerbit Hellow Pustaka, 2025)
Brotherhood among Muslims is a fundamental concept in Islamic teachings based on values of unity, compassion, and mutual assistance. The Qur'an and hadith explicitly emphasize the importance of strong, harmonious, faith-based relationships among Muslims. In QS Al-Hujurat verse 10, Allah SWT states,